Strategies to improve response rates to web surveys: A literature review - Sammut, Roberta; Griscti, Odette; Norman, Ian J. (International journal of nursing studies, 2021)
The development of the web survey has led to significant strides in questionnaire survey methodology, including its potential to substantially increase sample sizes at minimal costs. Despite its advantages, web surveys typically achieve lower response rates from participants compared to more conventional survey methods. The aim of this review was to evaluate strategies to increase the response rate to web surveys. CINAHL (EBSCO), MEDLINE Complete, the Cochrane database of systematic reviews, the Cochrane central register of controlled trials and Psych Info were searched, from inception to the 24th of June, 2021. The Boolean search phrase (Ti: Web survey* OR online survey* OR internet survey*) AND (Ti: response rate* OR nonresponse* or participation rate*) was used. This was supplemented by a secondary search of the reference lists. To be eligible for inclusion in the review, papers had to evaluate one or more strategies to improve response rates to web surveys. Experimental and quasi experimental studies were included in the review. A total of 159 papers were identified. Following removal of duplicates, and further screening by two independent reviewers, 45 papers met the inclusion and exclusion criteria, and were included in the final review. The use of e-mail pre-notification, email invitation and two reminders were found to increase response rates to web surveys as do the use of a semi-automatic log-in, a simple design and a short survey which takes around 10 min to complete. Incentives, including entry into a prize draw with a cash prize considered to be of value to the participants also increase response rates. Research studies are needed to explore whether the different strategies used by researchers with the intent to improve response rates are acceptable to potential participants and to evaluate the potential synergistic effect of combinations of several strategies identified in this review. Tweetable abstract: Email prenotification, email invitation, 2 reminders, simple 10 min design and lottery incentives improve response rates to web surveys